Changes in the Fitness Fatness Index following reduced exertion high-intensity interval training versus moderate-intensity continuous training in physically inactive adults - Daniel J. Leahy; Lance C. Dalleck; Lance C. Dalleck; Joyce S. Ramos (Frontiers Media S.A., 2022)
BackgroundMany adults do not reach the recommended exercise participation guidelines, often citing lack of time as a barrier. Reduced exertion high-intensity training (REHIT) is a mode of exercise that takes as few as 10 min and has been shown to be as effective as other modalities. The Fitness Fatness Index (FFI) is a recently developed index that is used to predict cardiovascular disease (CVD) risk. The aim of this study was to determine the efficacy of a REHIT vs. a traditional moderate-intensity continuous training (MICT) on FFI in physically inactive adults.MethodsThirty-two participants were randomized into one of two 8-week exercise intervention groups: (i) REHIT (n = 16); (ii) MICT (n = 16). The REHIT group performed 10 min of individualized cycling intervals on 2-4 days of the week. The MICT group were prescribed aerobic exercise at 50-65% of their heart rate reserve (HRR) on 3-5 days of the week. FFI was recorded at baseline and post 8-weeks, with FFI being calculated as cardiorespiratory fitness (CRF) (expressed as metabolic equivalents) divided by waist to height ratio (WtHR). A 1-unit increase in FFI was recognized as a clinically significant change in FFI.ResultsThe REHIT group showed significantly greater (+1.95, ±0.63) improvements in FFI compared to those in the MICT (+0.99, ±0.47) group (between group difference, p < 0.001). Furthermore, there was a greater proportion of participants who achieved a clinically significant change in FFI in the REHIT group (12/12, 100%) than in the MICT group (8/15, 53%) (between group difference, p = 0.01).ConclusionThis study suggests that REHIT may be a more efficacious exercise modality to increase FFI than MICT. This outcome is beneficial as the clinician can prescribe REHIT to physically inactive adults who cite lack of time as a barrier to physical activity participation and achieve significant reductions in CVD risk.